Manufacturing execution system of mineral processing based on Internet of things - Tianyou CHAI; Jinliang DING; Quan XU; Heng YUE (物联网学报)
With the development trend of intelligent,networked,integrated in the automation field of mineral processing industry,the longitudinal seamless fusion and integration from the Internet of things to the Internet of the full interconnection manufacturing network of mineral processing were constructed based on the actual demand of the enterprise management and control,data acquisition,transmission,storage and analysis framework were designed for industrial big data generated from mineral processing,the intelligent manufacturing execution system based on the Internet of things and the industrial cloud was developed.The new functions of integrated process production index optimization and decision making,equipment safety video surveillance and management,personnel vehicle location and tracking,energy management,mobile and remote monitoring,and so on were discussed.The manufacturing execution system based on the Internet of things and the industrial cloud was implemented and used in an iron and steel group.The effectiveness of the MES is verified.